O uso do system dynamics em um modelo de apoio a comercialização: uma aplicação à agricultura familiar. - Faulin, Evandro Jacóia (2004)
The family farmers play an important role in the Brazilian agricultural production. However, even though they occupy a prominent position in the agricultural production in Brazil, there are not management techniques specifically suitable to family farmers. Focusing on commercialization and vertical coordination, this dissertation has as main objective the development of management prescriptions related to procurement and marketing activities undertaken by family farmers. Computational simulation, based on System Dynamics methodology, was the main instrument to support procurement and marketing decisions. Interviews with thirty three vegetables family farmers and five of their main suppliers, all located in the region of São Carlos SP, provided the real data for the design of the computational model. The empirical research revealed that family farmers do not plan procurement and marketing appropriately, although they manage to compete with non-family production. The use of governance structures based on trust seems to be the main cause of their survival and success. The simulation based on System Dynamics helped the design of models that represent and help the decision making related the procurement and marketing by family farmers.